Total shoulder arthroplasty: risk factors for intraoperative and postoperative complications in patients with primary arthritis - Leschinger, Tim; Raiss, Patric; Loew, Markus; Zeifang, Felix (Journal of shoulder and elbow surgery, 2017)
Background - This study evaluated and identified risk factors for the development of intraoperative and postoperative surgical complications in total shoulder arthroplasty in patients with primary osteoarthritis. - Methods - We evaluated patient-specific factors, including age, sex, body mass index, prior nonarthroplasty surgery, smoking, alcohol consumption, and the American Society of Anesthesiologists (ASA) Physical Status Classification System in 275 patients (76 men, 199 women) with an average age of 68 years (range, 51-85 years). We categorized the number and severity of all complications and correlated these results with the patient-specific factors - Results - Twenty-seven complications (9.8%) in 275 shoulder arthroplasties were recorded. We identified 22 patients (8%) with category I complications and 5 (2.8%) with category II complications. Patients with an ASA score of 3 showed an increased likelihood of having a surgical complication compared with the control group with ASA scores of 1 and 2 (odds ratio, 4.28; 95% confidence interval, 1.79-10.20; P < .01). Smokers were more prone to surgical complications than nonsmokers (odds ratio, 5.08; 95% confidence interval, 1.96-13.11; P = .02). - Conclusion - Surgical complication rates after anatomic total shoulder arthroplasty in patients with primary osteoarthritis correlate with the patient's overall health status and nicotine consumption. This may be useful for predicting the likelihood of surgical complications and may thus prove important for clinicians to better assess and explain possible risks before surgery.
Available online 10 October 2016
Gesehen am 16.08.2018